Modern kazakh drama: ways and searches (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the most striking achievements and problemsin the development of national drama in 2015, where the author examinesthe current state and creative processes in its development, analyzes thecreative interaction with the drama-writer theater. The creative search ofthe Kazakh theater, as in a mirror reflectes the processes taking place in thisperiod in a society where one of the majorest events was the celebration ofthe 550th anniversary of the Kazakh Khanate and the formation of Kazakhstatehood, as well as a great victory in the Second World War